Cranial growth in infants─A longitudinal three-dimensional analysis of the first months of life. Issue 6 (June 2018) - Meyer-Marcotty, Philipp; Kunz, Felix; Schweitzer, Tilmann; Wachter, Barbara; Böhm, Hartmut; Waßmuth, Nina; Linz, Christian
Abstract: Purpose: In the first months of life, any deviation from a physiological growth pattern can cause skull deformity. As there has not been any longitudinal three-dimensional (3D) study investigating the physiological growth of the infant skull, the aim of the present study was to acquire such data. Materials and Methods: We performed 3D stereophotogrammetric scans of 40 infants without cranial asymmetry at four regular 2-month intervals from the 4th to the 10th month of age. Six growth-related parameters (circumference, length, width, height, cephalic index [CI; width-length ratio] and total head volume) were used to analyse skull growth longitudinally. Results: With exception of the CI, all parameters showed significant increases, with maximum percentage growth from the 4th to the 6th month. The CI initially remained unchanged until the 6th month, before showing a significant reduction that continued throughout the study period. Male infants had larger heads than female infants, but a similar width-length ratio at all measurement times. Conclusion: This prospective study is the first longitudinal 3D analysis to examine the physiological growth dynamics of infants' heads within the first months of life. Understanding patterns of skull growth in all three dimensions is important for gaining further insights into physiological and pathophysiological skull development.